Financial Performance of Islamic and Conventional Banks in Qatar: A ‎Comparative Analysis - SHIRAZI, NASIM SHAH; VAHAB, SHIRIN (International Journal of Islamic Economics and Governance, 2022)
The goal of bank performance evaluation is to guarantee that they efficiently ‎utilize resources. Financial performance analysis is a critical tool for recognizing ‎the bank's weaknesses and strengths across its numerous activities. The CAMELS ‎technique is regarded as a supervisory tool to evaluate bank performance based on ‎several aspects, according to the literature review. Regulators use on-site and off-‎site monitoring tools to assess a bank's financial stability. The CAMELS rating ‎system encourages transparency, evolution, and change in all financial ‎institutions. Furthermore, this method identifies the structural strengths and ‎weaknesses of financial organizations. This study conducts a comparative analysis ‎of Islamic and conventional banks in Qatar using the CAMELS rating scale from ‎‎2015 to 2020. We used a sample of 14 banks in Qatar, four of which were Islamic ‎while the others were conventional. The findings indicate that Islamic banks ‎showcase superior performance in Qatar while outperforming their conventional ‎counterparts in many variables. However, none of the banks in Qatar could obtain ‎a rating of 1, indicating areas of weaknesses that need to be worked on, particularly ‎in the area of liquidity, which was a critical factor for all banks. According to this ‎study, the Qatar Central Bank should improve the monitoring and screening of all ‎Islamic banks in Qatar. Furthermore, it is suggested that the Qatar central bank ‎employs the CAMELS system to track operations and field offices for banks ‎functioning to facilitate regular access to a stable banking sector. Banks can use ‎CAMELS to track their performance, and the necessary actions must be ‎undertaken.‎